ANALYSIS OF FINANCING EFFECTIVENESS IN SHARIA COOPERATIVES BMT BINA TANJUNG IN JEMBER - Bagus Qomaruzzaman Ratu Edi; Karim Budiono; Musaiyadi Musaiyadi (STIE Mandala Jember, 2022)
According to the Decree of the Minister (Kepmen) of Cooperatives and UKM of the Republic of Indonesia Number 91 of 2004 Sharia Financial Services Cooperatives (KJKS) are cooperatives whose business activities are engaged in financing, investment, and savings according to the pattern of profit sharing (sharia). In carrying out its function as a property development house, the BMT Bina Tanjung Sharia Cooperative encourages saving activities and supports the financing of economic activities. The objectives of this study are (1) to determine the effectiveness of sharia financing that has been carried out by the BMT Bina Tanjung Sharia Cooperative in Jember; (2) Knowing the Net Performing Loan (NPL) financing of Sharia Cooperative BMT Bina Tanjung in Jember. This study uses the analysis of Financing Effectiveness and Net Performing Loan Ratio (NPL). By using the purpose sample technique with 30 selected customer respondents, the results include; (a) The effectiveness of financing distribution at the BMT Bina Tanjung Sharia Cooperative in Jember resulted in an average disbursement of financing to customers in the January 2021 to December 2021 range of 105.5%. This means that if the achievement results are more than 100%, then the financing of the BMT Bina Tanjung Sharia Cooperative in Jember is in the Very Effective category, (b) The Net Performing Loan (NPL) calculation shows that the NPL ratio of financing in the BMT Bina Tanjung Jember Sharia Cooperative is above the Bank's ideal number. Indonesia is 5%, which is 7.3%, meaning that there are more bad loans than current loans.